2021
DOI: 10.1177/01945998211032113
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Receiving Necessary Hearing Care Among US Children

Abstract: Objective We aim to clarify the national scope of unmet pediatric hearing care needs and identify specific barriers to hearing care. Study Design Cross-sectional study of a nationally representative data set. Setting This study is based on the combined 2016 and 2017 National Survey of Children’s Health. This survey covers the physical and emotional health, access to care, and social context of US children and adolescents aged 0 to 17 years. Methods Analysis of parent-reported responses of children’s hearing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Whether these services or settings have improved is difficult to monitor due to limited data on outcomes [39,40]. In addition to sometimes inappropriate or inadequate services, most DHH students-notably hard of hearing students-may not receive any services at all [41]. This is particularly true for rural DHH children [42] and for DHH children during the COVID pandemic [43].…”
Section: Full Inclusionmentioning
confidence: 99%
“…Whether these services or settings have improved is difficult to monitor due to limited data on outcomes [39,40]. In addition to sometimes inappropriate or inadequate services, most DHH students-notably hard of hearing students-may not receive any services at all [41]. This is particularly true for rural DHH children [42] and for DHH children during the COVID pandemic [43].…”
Section: Full Inclusionmentioning
confidence: 99%
“… Point 1 In HPV‐associated oropharyngeal squamous cell carcinoma (OPSCC), Black and nonprivately insured patients are less likely to receive primary surgery when compared with White or privately insured patients 1 Points 2 and 3 Deaf or hard‐of‐hearing children with unmet hearing care needs are more likely to be from non‐White backgrounds 2 Black patients undergo cochlear implant evaluation and cochlear implantation at rates disproportionately lower than expected based on local demographics.…”
mentioning
confidence: 99%
“…Deaf or hard‐of‐hearing children with unmet hearing care needs are more likely to be from non‐White backgrounds 2 …”
mentioning
confidence: 99%
“…4 Hearing-related services for children, a particularly vulnerable group, face multiple challenges and barriers in providing access to these much-needed services. 5 Disparities in otolaryngology care outcomes are also seen in rural communities, especially related to head and neck cancers. Several epidemiologic studies that investigated a variety of head and neck cancers revealed that rurality may affect access to specialized treatment protocols or result in delayed diagnosis and more advanced disease.…”
mentioning
confidence: 99%
“…The need for basic otolaryngology care is particularly evident in vulnerable and marginalized groups, such as the diverse urban homeless population in Vatican City, which includes individuals from over 60 countries 4 . Hearing‐related services for children, a particularly vulnerable group, face multiple challenges and barriers in providing access to these much‐needed services 5 . Disparities in otolaryngology care outcomes are also seen in rural communities, especially related to head and neck cancers.…”
mentioning
confidence: 99%